2017
DOI: 10.1308/rcsann.2017.0010
|View full text |Cite
|
Sign up to set email alerts
|

Lateral thyroid cartilage thyrotomy approach to an embedded paraglottic fishbone

Abstract: Fishbones are of particular interest to otolaryngologists. Most fishbones can be removed transorally or via endoscopic guidance. Transcervical neck exploration is occasionally necessary, especially in cases of an embedded foreign body. Computed tomography is the most sensitive and specific imaging modality for identifying embedded fishbones. To our knowledge, this is the first reported case of a laryngeal foreign body embedded in the paraglottic space that was removed using an open approach via a lateral thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Interestingly, Wong et al reported a case of an open approach via a creation of lateral thyroid cartilage window in managing an embedded paraglottic FB. The perichondrium of thyroid cartilage was sutured after removing the FB [13].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wong et al reported a case of an open approach via a creation of lateral thyroid cartilage window in managing an embedded paraglottic FB. The perichondrium of thyroid cartilage was sutured after removing the FB [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hemitiroidecotmy has been proposed for the retrieval of a FB stuck in the thyroid gland [26]. For FB located in the paraglottic space, both anterior and posterior approaches to the laryngeal cartilages have been described [27][28][29][30]. With technological advances, imaging-guided approaches have been promisingly introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors previously discussed transcervical approach including laryngofissure and posterolateral approach in deeply embedded foreign body. 14,15) They suggested the usefulness of transcervical approach especially in patients who failed to remove foreign body endoscopically. But in current case, the needle was located far from skin more than 1 cm and it was more close to approach from visceral space, so we did not consider transcervical approach initially.…”
Section: Discussionmentioning
confidence: 99%